2018
DOI: 10.1074/jbc.ac118.002052
|View full text |Cite
|
Sign up to set email alerts
|

Myeloid-derived growth factor is a resident endoplasmic reticulum protein

Abstract: Human myeloid-derived growth factor (MYDGF, also known as C19orf10) is named based on its identification as a secreted monocyte/macrophage-derived mediator of cardiac repair following myocardial infarction in mice. Homologs of MYDGF, however, are present in organisms throughout and outside of the animal kingdom, some of which lack hematopoietic and circulatory systems. Moreover, the UPF0556 protein domain, which defines these homologs, lacks a known structure. As a result, the functions and properties of MYDGF… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
23
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(25 citation statements)
references
References 38 publications
1
23
1
Order By: Relevance
“…Our goal in initiating these studies was to determine the solution structure of hMYDGF as a model for other members of the widespread MYDGF/UPF0556 family of proteins and to provide insights into the functions of MYDGF as a well-conserved resident ER protein 1 and as a paracrine/autocrine survival factor with therapeutic potential after myocardial infarction 7,32 . We found that hMYDGF consists of a β-sandwich occluded at one edge by an α-helical turn and small β-sheet (Fig.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Our goal in initiating these studies was to determine the solution structure of hMYDGF as a model for other members of the widespread MYDGF/UPF0556 family of proteins and to provide insights into the functions of MYDGF as a well-conserved resident ER protein 1 and as a paracrine/autocrine survival factor with therapeutic potential after myocardial infarction 7,32 . We found that hMYDGF consists of a β-sandwich occluded at one edge by an α-helical turn and small β-sheet (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Human myeloid-derived growth factor (hMYDGF) is a member of the widely distributed MYDGF family of proteins found in organisms as distant as protozoans 1 . In humans, MYDGF is abundant in nearly 200 different tissues, fluids, and cell lines as compiled by Proteomics DB, a repository of quantitative proteomics data 2 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…MYDGF, previously named c19orf10 (chromosome 19 open reading frame 10), is a poorly characterized protein, which was identified as a paracrine-acting protein that is secreted by monocytes and macrophages 4 . MYDGF is evolutionarily highly conserved and resides in the endoplasmic reticulum (ER), in the Golgi and extracellularly 6 . According to its primary amino acid sequence, MYDGF does not belong to any known cytokine or growth factor family.…”
Section: Introductionmentioning
confidence: 99%
“…According to its primary amino acid sequence, MYDGF does not belong to any known cytokine or growth factor family. Human MYDGF has 142 amino acids and consists of an N-terminal 31-residue-long signal peptide and the MYDGF protein sequence containing a C-terminal KDEL-like ER retention sequence 6 . Even though MYDGF’s effects on cardiac tissue repair have been revealed and downstream signaling pathways have been identified 4 , the MYDGF receptor(s) or binding partners mediating these effects remain unknown.…”
Section: Introductionmentioning
confidence: 99%